Determining the Relationship Between the Impairment of Selective Voluntary Motor Control and Gait Deviations in Children With Cerebral Palsy Using Simple Video-Based Analyses - Sardogan, Cansu; Muammer, Rasmi; AKALAN, NAZİF EKİN; Sert, Rukiye; Bilgili, Fuat (Elsevier Ireland Ltd., 2021)
Background: The impairment of selective voluntary motor control (SVMC) in children with cerebral palsy (CP) has been shown to correlate with their gait characteristics using complex 3D gait analysis systems (3DGA); however, this relationship has not been investigated using simple video-based observational gait analysis (VBOGA). The aim of this study was to determine the relationship between VBOGA and SVMC of the lower extremities in children with CP. Methods: Forty-two CP children 10.9 +/- 5.7 years old with Gross Motor Function Classification System (GMFCS) levels I-III participated in the study. Their gait characteristics were assessed using the Edinburgh Visual Gait Score (EVGS), and selective voluntary motor control was tested using the Selective Control Assessment of the Lower Extremity (SCALE). Spearman's rho correlation test with Cohen's classification were used in the statistical analyses. Results: The GMFCS levels (r = 0.604, p < 0.001), foot clearance (r = -0.584. p < 0.001), and maximum ankle dorsiflexion (r = -0.567, p < 0.001) during the swing phase had strong correlations with total SCALE scores. There was also a moderate correlation between total SCALE scores and total EVGS (r = -0.494, p < 0.001), knee extension in the terminal swing phase (r = -0.353, p < 0.001), peak sagittal trunk position (r = -0.316, p < 0.005), and maximum lateral shift (r = -0.37, p < 0.001). Conclusion: Impaired lower extremity SVMC was noticeably related to the foot and ankle movements in the swing phase and initial stance during walking as well as the total EVGS scores and sagittal and frontal trunk movements. The SCALE correlations with VBOGA were similar those observed in the complex 3DGA in the literature; therefore, we suggest that SVMC impairment of gait could be evaluated using simple VBOGA. These findings may help to tailor physical therapy programs for CP children to increase their motor control and walking quality.
Keywords: SCALE; Cerebral Palsy; Selective Motor Control; Gait; Edinburgh Visual Gait Score